Dream journaling: stability and relation to personality factors - Schredl, Michael; Göritz, Anja (Dreaming, 2020)
Cross-sectional surveys have indicated that about 5% of the survey participants recorded their dreams at least once a month. Studies have shown that dream recording is related to dream recall frequency, openness to experience, and low conscientiousness, indicating a distinct personality type of dream journalists. The findings of the first longitudinal study (N = 739 persons; 429 woman, 310 men; M-age: 48.76 +/- 15.16 years) over a 2-year period on this topic indicate that dream recording is a very stable trait and that the 3 variables (dream recall frequency, openness to experience, and low conscientiousness) are still related to dream recording frequency if the trait aspect (previously measured dream recording frequency) is statistically controlled. Future studies should shed light on the motivations that stimulate dreamers to carry out the arduous task of recording dreams immediately upon awakening.
Gesehen am 26.11.2020